Signaling pathways in lymphoma: pathogenesis and therapeutic targets. (October 2013) - Arita, Adriana; McFarland, Daniel C; Myklebust, June H; Parekh, Samir; Petersen, Bruce; Gabrilove, Janice; Brody, Joshua D
Lymphoma is the fifth most common cancer in the USA. Most lymphomas are classified as non-Hodgkin's lymphoma, and nearly 95% of these cancers are of B-cell origin. B-cell receptor (BCR) surface expression and BCR functional signaling are critical for survival and proliferation of both healthy B cells, as well as most B-lymphoma cells. Agents that inhibit various components of the BCR signaling pathway, as well as parallel signaling pathways, are currently in clinical trials for the treatment of various lymphoma subtypes, including those targeting isoforms of PI3K, mTOR and BTK. In this review, we describe the signaling pathways in healthy mature B cells, the aberrant signaling in lymphomatous B cells and the rationale for clinical trials of agents targeting these pathways as well as the results of clinical trials to date. We propose that the entry into a kinase inhibitor era of lymphoma therapy will be as transformative for our patients as the advent of the antibody or chemotherapy era before it.